Involvement of Stat1 in the Phagocytosis of M. avium - Sabrina Dominici; Giuditta Fiorella Schiavano; Mauro Magnani; Costantina Buondelmonte; Angela Gabriela Celeste; Giorgio Brandi (Clinical and Developmental Immunology)
Mycobacterium avium is an intracellular pathogen preferentially infecting human macrophages where they activate the JAK/STAT1 pathway. This activation enhances the survival of infected cells, but, at the same time, makes macrophages optimal targets for drugs development against p-tyr701stat1. In this study, we demonstrate that the fast and transient activity of the JAK/STAT1 pathway occurs immediately after macrophages internalization of heat-killed M. avium or inert particles. Furthermore, we show that a persistent Stat1 pathway activation occurs only when an intracellular M. avium infection is established in macrophages. These results strongly indicate different mechanisms of p-tyr701Stat1 activation. In particular, here we report findings aiming at explaining the short-time enhancement of p-tyr701Stat1 and shows its predominant relationship with FcγRs engagement during the internalization process. Furthermore, we demonstrate that opsonized live M. avium is phagocytosed by macrophages involving membrane receptors not related with JAK/STAT1 signalling pathway. On the contrary, heat-inactivated bacilli or latex particles seem to be internalized only after involvement of FcγRs and subsequent Stat1 phosphorylation.